2021
DOI: 10.1002/edn3.259
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of sedimentary plant DNA is related to lake water chemistry

Abstract: Little is currently known about preservation of plant DNA in lake sediments. Most prior information originates from laboratory experiments while systematic field‐based studies are still lacking. Here, we used the “g” and “h” universal primers for the P6 loop region of the chloroplast trnL (UAA) intron to amplify plant DNA from 219 lake surface sediments from China and Siberia. We introduce (i) the percentage of sequence counts with the best identity ≥95%, (ii) weighted average identity, (iii) weighted average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 113 publications
0
22
0
2
Order By: Relevance
“…In our study, we detected 103 unique macrophyte ASVs from floating, submerged, and wetland taxa by using the trnL P6 loop as a metabarcode applied to surface and core sediments from Siberian and Chinese lakes. Despite the overall high number of recovered ASVs in our dataset, the macrophyte richness in the surfacesediment data varies strongly, which can be either caused by differences in DNA quality of the samples (Jia et al 2021) and related differences in metabarcoding success and/or by assembly rules that naturally affect macrophyte richness. The taxonomic resolution of the 103 ASVs is very good with a detection of 99% of ASVs to genus (67%) or species (32%) level, although the taxonomic resolution of the g-h amplified trnL P6 loop (Taberlet et al 2007) is lower compared to its encompassing longer trnL fragment (Zhu et al 2015).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our study, we detected 103 unique macrophyte ASVs from floating, submerged, and wetland taxa by using the trnL P6 loop as a metabarcode applied to surface and core sediments from Siberian and Chinese lakes. Despite the overall high number of recovered ASVs in our dataset, the macrophyte richness in the surfacesediment data varies strongly, which can be either caused by differences in DNA quality of the samples (Jia et al 2021) and related differences in metabarcoding success and/or by assembly rules that naturally affect macrophyte richness. The taxonomic resolution of the 103 ASVs is very good with a detection of 99% of ASVs to genus (67%) or species (32%) level, although the taxonomic resolution of the g-h amplified trnL P6 loop (Taberlet et al 2007) is lower compared to its encompassing longer trnL fragment (Zhu et al 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Besides the dominance of a specific Stuckenia ASV, the globally distributed emergent macrophyte P. australis (common reed) is abundant in lakes with the highest conductivity (up to 57,000 μS cm À1 ) because it can withstand saline conditions (Köbbing et al 2013) and also because of the co-occurrence of beneficial rhizospheric microbial communities (Srivastava et al 2014). Differences in DNA preservation tested on a larger metabarcoding data of 219 surface samples (Stoof-Leichsenring et al 2020) that include aquatic and terrestrial plants indicate that conductivity and lake size significantly explain recovered total plant richness from surface sediment DNA (Jia et al 2021). Specifically, at high ion concentrations and partly warmer winter temperatures detected in a few Chinese lakes, poor sedDNA preservation might cause a decrease the recovery of the plant DNA signal in general (Jia et al 2021).…”
Section: Temperature and Conductivity Are Significant Predictors Of M...mentioning
confidence: 99%
See 1 more Smart Citation
“…We recommend that more exploratory work of extracellular DNA be conducted to evaluate the potential of developing bioindicators from different environments (i.e., pelagic, littoral or terrestrial) across a wider range of lake conditions. For example, a recent study by Jia et al (2021) suggests that lake water conditions (i.e., pH and conductivity) can influence the preservation of extracellular DNA. More work is also needed to evaluate the congruence between extracellular and intracellular DNA fractions on sediment cores spanning longer time period to better understand the value of extracellular DNA when studying older sedDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies comparing the morphology and DNA-based methods for diatom identifications have worked with sediment cores from freshwater systems where the preservation of valves as well as DNA is expected to be favorable. A recent study about plant DNA preservation in the sediments suggested that lakes with pH 7-9 and conductivities with 100-500 μS/cm may have better preservation of sedimentary DNA compared to lakes with higher or lower values of latter measures (Jia et al, 2021). However, sedimentary DNA studies to identify diatom (Kang et al, 2021) and ostracod (Echeverría-Galindo et al, 2021) communities indicated the potential of DNA metabarcoding in the environmental settings of the lake Nam Co with conductivity >1,400 μS/cm and pH ~9.…”
Section: Introductionmentioning
confidence: 99%